2019
DOI: 10.1038/s41385-018-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-106a deficiency attenuates inflammation in murine IBD models

Abstract: Pro-inflammatory cytokine TNFα antagonizes regulatory T cell (Treg) suppressive function with a measurable reduction of IL-10 protein secretion. Tregs are critical to suppress excessive immune activation, particularly within the intestine where high antigenic loads elicit chronic subclinical immune activation. Employing a TNFα-driven murine inflammatory bowel disease (IBD) model (TNF ΔARE/+ ), which mirrors the Treg expansion and transmural ileitis seen in Crohn’s disease, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Extracellular vesicles containing miR-146a ameliorates experimental TNBS caused colitis by targeting TRAF6 and IRAK139. MiR-106a knockout attenuated chronic murine ileitis via promoting Treg induction and suppressive function and IL-10 production 40 . These studies indicated that various miRNAs played critical role in the pathogenesis and treatment of IBD, and their effects may vary based on the age (children or adults), the symptoms (chronic or acute), the status of IBD (active or inactive), and the pathogenesis of colitis and so on 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles containing miR-146a ameliorates experimental TNBS caused colitis by targeting TRAF6 and IRAK139. MiR-106a knockout attenuated chronic murine ileitis via promoting Treg induction and suppressive function and IL-10 production 40 . These studies indicated that various miRNAs played critical role in the pathogenesis and treatment of IBD, and their effects may vary based on the age (children or adults), the symptoms (chronic or acute), the status of IBD (active or inactive), and the pathogenesis of colitis and so on 41 .…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are emerging as vital modulators of gene expression in the immune response which control the differentiation and function of Treg cells [28, 29]. Evidence also showed that DECs could secrete miRNAs (miR-155 and miR-146a) to regulate inflammatory response to LPS [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, microRNAs mediate the modulation of gut microbiome composition and their secretion of secondary metabolites; the aberrant microRNA expression and dysbiosis of gut intestinal microbiota are strongly correlated with a variety of intestinal diseases, particularly IBD and colorectal cancer [ 97 , 98 , 99 ]. Studies on miR-194-5p, miR-148-3p, and miR-27b-3p reveal that these microRNAs could be intermediates between Enterobacteriaceae and gut inflammation, and they have a strong correlation with Proteobacteria, which were previously reported to be abundant in IL-10 knockout mice and IBD patients, indicating their roles as mediators in the pathogenesis of Proteobacteria and intestinal inflammation [ 11 , 100 ]. Relying on fecal microbiota transplantation, the germ-free mice received intestinal microbes from wild-type donor, which exhibited a significant difference in their fecal microRNA profiles, and several other microRNAs, such as miR-144, miR-519, and miR-211, have been considered as important modulators of gut microbiota and biomarkers for Crohn’s disease, verified in the adult CD patients [ 101 ].…”
Section: Microrna In Modulating Gut Intestinal Microbiotamentioning
confidence: 99%